Cost variation analysis of antimalarial drugs available in India - Kumar, Lalit; Dinkar, Jyoti Kumar; Mohan, Lalit; Dikshit, Harihar (International Journal of Research in Medical Sciences, 2017)
Background: Malaria has been a problem in India for centuries. There are innumerable brands of antimalarial present in the market. Malaria can be extremely fatal if not treated promptly. Costly drugs can lead to economic burden which results in decreased compliance or even non-compliance. Non-compliance leads to incomplete treatment which tends to increase morbidity. Increase in the patient medication cost was found to be associated with decreased adherence to prescription medication. Hence this study was done to assess the cost variation of malaria therapy. Methods: The maximum and minimum price of each brand of the drug in INR was noted by using CIMS January to April 2017 edition and Drug Today January to March 2017, Vol 2. The cost ratio and the percentage cost variation for individual drug brands was calculated. The cost of 10 tablets was calculated in case of oral drug and the cost of 1 ampoule or vial was noted in case of injectable drug. At last the cost ratio and % cost variation of various brands was compared. Results: The analysis of data reflected a considerable cost variation among antimalarial drugs. Artemether injection showed the highest cost ratio and cost variation (cost ratio = 16.96 and % cost variation = 1596). Overall injectable antimalarials showed considerable cost variation as compared to oral antimalarial agents. Chloroquine which is one of the most used antimalarial showed very low values for cost variation and cost ratio. Conclusions: The analysis showed that there is not much significant price variation among oral antimalarial drugs. The maximum variation shown by oral antimalarial was found to be for fixed dose combination of Artemether and Lumefantrine [cost ratio>2 (2.03) and % price variation >100 (103.7)]. But there was significant price variation among injectable antimalarial. Injectable antimalarials are often the choice of drug when dealing with critically ill malaria patients specially when suffering from complicated malaria. So, such significant price variation creates burden on poor patients economically which leads to non-compliance and hence increased morbidity and mortality due to incomplete treatment.